HOSPITAL STAFFING, ORGANIZATION, AND QUALITY OF CARE: CROSS-NATIONAL FINDINGS - Mohammed Khalil Alkhaibari ,Aeshah Faiz T Alsubaie , Eman Ahmed Al shareef; Abdulmajeed Mohammed Alabdan,Turki meshal Alamri, Abdulaziz Y. Aldughaither (Chelonian Research Foundation, 2023)
This paper presents a cross-national comparison of hospital staffing, organization, and quality of care. The study aims to explore how these factors differ across different countries and what impact they have on the quality of care provided to patients. The research methodology involved a review of existing literature and data from reputable sources to analyze the current state of hospital staffing and organization in various healthcare systems. The results indicate significant variations in staffing levels, organizational structures, and quality of care across different countries. The discussion highlights the implications of these findings for healthcare policy and practice. Overall, this study contributes to the understanding of how hospital staffing and organization influence the quality of care provided to patients in different healthcare settings. Keywords: hospital staffing, organization, quality of care, cross-national comparison, healthcare systems.